Disturbance is more important than seeding or grazing in determining soil microbial communities in a semiarid grassland. (15th April 2020) - Farrell, Hannah L.; Barberán, Albert; Danielson, Rachel E.; Fehmi, Jeffrey S.; Gornish, Elise S.
Abstract : A primary goal of ecological restoration is often to return processes and functions to degraded ecosystems. Soil, while often ignored in restoration, supports diverse communities of organisms and is a fundamental actor in providing ecosystem processes and services. We investigated the impact of seeding and livestock grazing on plant communities, soil microorganisms, and soil fertility 3 years after the restoration of a disturbed pipeline corridor in southeastern Arizona. The initial soil disturbance and topsoil treatment, regardless of seeding or grazing, was the most influential factor in determining differences in both plant and microbial communities. Compared with the control, the disturbed and restored sites had greater plant species richness, greater total herbaceous plant cover, greater soil organic matter, higher pH, and differed in soil nutrients. Bacteria and fungi appeared to generally correlate with micro‐environment and soil physiochemical properties rather than specific plant species. The undisturbed control had a smaller proportion of bacterial functional groups associated with the breakdown of plant biomass (polysaccharide decomposition) and a smaller proportion of arbuscular mycorrhizal fungi (AMF) compared with disturbed and restored sites. The ability of the unseeded disturbed site to recover robust vegetation may be due in part to the high presence of AMF. These differences show selection for soil microorganisms that thrive in disturbed and restored sites and may contribute to increased plant productivity. Restoration of specific plant species or ecological processes and services would both benefit from better understanding of the impacts of disturbance on soil microorganisms and soil fertility.